Multicenter Initial Guidance on Use of Antivirals for Children With Coronavirus Disease 2019/Severe Acute Respiratory Syndrome Coronavirus 2. (22nd April 2020) - Chiotos, Kathleen; Hayes, Molly; Kimberlin, David W; Jones, Sarah B; James, Scott H; Pinninti, Swetha G; Yarbrough, April; Abzug, Mark J; MacBrayne, Christine E; Soma, Vijaya L; Dulek, Daniel E; Vora, Surabhi B; et al.
Abstract: Background: Although coronavirus disease 2019 (COVID-19) is mild in nearly all children, a small proportion of pediatric patients develop severe or critical illness. Guidance is therefore needed regarding use of agents with potential activity against severe acute respiratory syndrome coronavirus 2 in pediatrics. Methods: A panel of pediatric infectious diseases physicians and pharmacists from 18 geographically diverse North American institutions was convened. Through a series of teleconferences and web-based surveys, a set of guidance statements was developed and refined based on review of best available evidence and expert opinion. Results: Given the typically mild course of pediatric COVID-19, supportive care alone is suggested for the overwhelming majority of cases. The panel suggests a decision-making framework for antiviral therapy that weighs risks and benefits based on disease severity as indicated by respiratory support needs, with consideration on a case-by-case basis of potential pediatric risk factors for disease progression. If an antiviral is used, the panel suggests remdesivir as the preferred agent. Hydroxychloroquine could be considered for patients who are not candidates for remdesivir or when remdesivir is not available. Antivirals should preferably be used as part of a clinical trial if available. Conclusions: Antiviral therapy for COVID-19 is not necessary for the great majority of pediatric patients. For those rare cases of severe or critical disease, this guidance offers an approach for decision-making regarding antivirals, informed by available data. As evidence continues to evolve rapidly, the need for updates to the guidance is anticipated. Abstract : Supportive care is sufficient for most pediatric patients with coronavirus disease 2019 given the overwhelming tendency toward mild illness in children. Decision-making regarding antiviral therapy for severely/critically ill children should weigh individual risks and benefits, informed by available evidence.